MENUMBUHKAN POTENSI, MENGASAH KEMAMPUAN: REFLEKSI PERKEMBANGAN PESERTA DAURAH DI MASJID FATHUN QARIB - Dewi Permata Sari; Maili Okta Vera; Safrilsyah (Kampus Akademik Publiser, 2025)
The daurah program is a coaching space designed to grow the potential and hone the abilities of participants, both in terms of knowledge and morals. This article shows the development process of participants during the daurah, starting from understanding the material, discipline, until they one by one succeeded in achieving their respective targets. With a structured yet warm approach, participants showed significant progress in a relatively short time. This reflection not only records achievements, but also describes the growth process that is gone through with enthusiasm, learning together, and sincerity in seeking knowledge.